JMP®, JMP IN® , and JMP Serve ™ - C.H. Spiegelman (Chemometrics and Intelligent Laboratory Systems, 1991)
Background and aims Indonesia harbors extraordinary non-human primate (NHP) diversity, yet deforestation, ecotourism, illegal wildlife trade, and urban encroachment are intensifying human-NHP contact, elevating pathogen spillover risk. This review synthesizes evidence on NHP-associated zoonoses within a One Health framework and proposes an integrated biosurveillance roadmap. Methods A structured search of PubMed, Scopus, and Web of Science (2000-2025), informed by the PRISMA-ScR framework and using pre-specified host, geographic, and pathogen search terms, was conducted and supplemented by grey literature from WHO, FAO, BPOM, and Indonesia's Ministry of Health. Results Five priority zoonotic pathogen categories were identified: Plasmodium knowlesi malaria, Macacine alphaherpesvirus 1 (Herpes B virus), simian foamy virus, Mycobacterium tuberculosis complex, and zoonotic gastrointestinal parasites. Surveillance capacity is fragmented and NHP-specific pathogen monitoring is absent from national systems. Conclusions NHP-derived zoonoses represent a growing public health threat in Indonesia. A NHP-inclusive One Health surveillance system integrating molecular diagnostics, geographic information systems, and cross-sectoral regulatory coordination is urgently needed.